New Biocompatible β‐Phosphorylated Linear Nitrones Targeting Mitochondria: Protective Effect in Apoptotic Cells. (28th March 2023) - Culcasi, Marcel; Delehedde, Caroline; Esgulian, Mathieu; Cassien, Mathieu; Chocry, Mathieu; Rockenbauer, Antal; Pietri, Sylvia; Thétiot‐Laurent, Sophie
Abstract: The mitochondrion, an essential organelle involved in cellular respiration, energy production, and cell death, is the main cellular source of reactive oxygen species (ROS), including superoxide. Mitochondrial diseases resulting from uncontrolled/excess ROS generation are an emerging public health concern and there is current interest in specific mitochondriotropic probes to get information on in‐situ ROS production. As such, nitrones vectorized by the triphenylphosphonium (TPP) cation have recently drawn attention despite reported cytotoxicity. Herein, we describe the synthesis of 13 low‐toxic derivatives of N ‐benzylidene‐1‐diethoxyphosphoryl‐1‐methylethylamine N ‐oxide (PPN) alkyl chain‐grafted to a pyridinium, triethylammonium or berberinium lipophilic cation. These nitrones showed in‐vitro superoxide quenching activity and EPR/spin‐trapping efficiency towards biologically relevant free radicals, including superoxide and hydroxyl radicals. Their mitochondrial penetration was confirmed by 31 P NMR spectroscopy, and their anti‐apoptotic properties were assessed in Schwann cells treated with hydrogen peroxide. Two pyridinium‐substituted PPNs were identified as potentially better alternatives to TPP nitrones conjugates for studying mitochondrial oxidative damage. Abstract : The repertoire of mitochondrion‐targeted nitrones has been expanded by the synthesis of 13 N ‐benzylidene‐1‐diethoxyphosphoryl‐1‐methylethylamine N ‐oxide derivatives vectorized by grafting varying aliphatic linkers bearing a terminal pyridinium, tetraethylammonium or berberinium cation. Exploring an array of physicochemical, biochemical, and biological properties allowed two novel hit nitrones to be selected that could be useful probes in reactive oxygen‐species‐related mitochondrion studies.